Classic Lego mindstorms project and software tools : award-winning designs from master builders - Ferrari, Mario (Syngress, 2006)
This Book/DVD kit meets the growing demand from Lego Mindstorms fans for additional projects that can be built from their existing Lego Mindstorms kits. Over 40 new projects will appeal to that dedicated segment of the Lego audience that are committed to the RIS 1.x and 2.x standards. The book contains seven complete "Master" projects that illustrate how great design, planning, mechanical engineering skills, and programming can create stunning and award winning projects. The DVD contains instruction for over 40 projects in Adobe PDF form, a full suite of Lego software tools, and RCX/NQC code files. The projects range from the simple to the sophisticate, and are perfect for self-learning. * Complete new set of projects for the RIS 1.x and 2.x * This Book and DVD package delivers a complete kit, perfect for team projects as well as those individual building * packed full with award winning designs that will inspire any Mindstorms fan